Teacher support and school proficiency - Bermeo, Caren Gabriela Castillo (2025)
This dissertation examines the perception of teacher support as a key factor in the economics of education, emphasizing its dual potential to either foster learning and socioemotional development or reinforce existing educational inequalities. While traditional research has focused on structural determinants such as resources, socioeconomic status, or school climate, recent studies highlight the importance of daily interactions between students and teachers. Perceived teacher support understood as the guidance, care, and motivation provided by teachers directly affects engagement, academic performance, and long-term trajectories, and is closely linked to the development of socioemotional skills captured by the Big Five model. However, the distribution of support is not uniform: it is often conditioned by prior academic achievement, student behavior, and classroom dynamics, which may disadvantage historically vulnerable groups. In highly unequal contexts such as Brazil, this raises the question of whether teacher support acts as a compensatory mechanism or a factor that amplifies disparities. Drawing on longitudinal datasets and multilevel analyses, the dissertation integrates two complementary studies: one on the relationship between perceived support, mathematics performance, and socioemotional skills over time; and another on short-term variations in perceived support within classrooms, shaped by performance, climate, and teacher attributes. Together, the findings underscore the dynamic nature of teacher support and its central role in shaping educational equity, offering methodological, empirical, and policy contributions to the field.